Analysis of the Use of the Tandem Application as a Bipa Learning Media for Foreign Speakers - Siregar, Ulfah Maulidiah Marwah; Octafriyanda, Dinda; Hutagaol, Romauli; Pangaribuan, Rina Lusiana; Sunarti, Sunarti; Harahap, Safinatul Hasanah (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
This research analyzes the use of the Tandem application as a medium for learning Indonesian for Foreign Speakers (BIPA) through the roomchat feature. The aim of this study is to evaluate the effectiveness of the Tandem application in improving Indonesian language skills for non-native speakers and understand the extent to which the roomchat feature can support the learning process. This study is an empirical study with a descriptive qualitative approach. Data is presented and described with comprehensive meaning. The data for this study was taken using observation and interview techniques. The results of the research show that the use of the Tandem application significantly helps improve the speaking and writing skills of BIPA students. The roomchat feature in this application allows intensive and real-time interaction between native Indonesian speakers and students, thereby creating a communicative learning environment and supporting direct language practice. This study concludes that the Tandem application is an effective and innovative tool in BIPA learning, and provides recommendations for teachers to utilize similar technology in the teaching process. It is hoped that these findings can contribute to the development of more interactive and interesting language learning methods in the future.